Role of the Breast Cancer Resistance Protein (BCRP/ABCG2) in Drug Transport—an Update - Mao, Qingcheng; Unadkat, Jashvant D. (The AAPS journal, 2015)
The human breast cancer resistance protein (BCRP, gene symbol ABCG2 ) is an ATP-binding cassette (ABC) efflux transporter. It was so named because it was initially cloned from a multidrug-resistant breast cancer cell line where it was found to confer resistance to chemotherapeutic agents such as mitoxantrone and topotecan. Since its discovery in 1998, the substrates of BCRP have been rapidly expanding to include not only therapeutic agents but also physiological substances such as estrone-3-sulfate, 17β-estradiol 17-(β- d -glucuronide) and uric acid. Likewise, at least hundreds of BCRP inhibitors have been identified. Among normal human tissues, BCRP is highly expressed on the apical membranes of the placental syncytiotrophoblasts, the intestinal epithelium, the liver hepatocytes, the endothelial cells of brain microvessels, and the renal proximal tubular cells, contributing to the absorption, distribution, and elimination of drugs and endogenous compounds as well as tissue protection against xenobiotic exposure. As a result, BCRP has now been recognized by the FDA to be one of the key drug transporters involved in clinically relevant drug disposition. We published a highly-accessed review article on BCRP in 2005, and much progress has been made since then. In this review, we provide an update of current knowledge on basic biochemistry and pharmacological functions of BCRP as well as its relevance to drug resistance and drug disposition.